KAJIAN TENTANG PELANGGAN PENGGANGGU (JAY CUSTOMER) DALAM PERSPEKTIF ISLAM STUDI KASUS PELANGGAN DISTRIBUTOR TEXTIL TOKO SANDANG SELENDANG FAJAR DI CIAWI TASIKMALAYA - Ratih Tresnati; Neneng Nurhasanah (Jurnal Manajemen Bisnis Performa, 2017)
There are various characters of customers. There are customers with annoying character and also arrogant, that condition happens in Selendang Fajar Ciawi Tasikmalaya Store, a textile product distributor in Ciawi Tasikmalaya. Method that being used in this article is pra survey supported by in depth literature review. On Business world, producers/distributors can not avoid the existence of Jay Customer, such as: customers who stealing/shoplifting, breaking rules; expressing anger, emotional, threatening or demeaning; arguing with employee of the store; ruining facilities and infrastructure; refusing to pay products/services that they bought. Jay Customer can be “Profitable Customer” if employee can handle their behavior, where those abilities can be given by the company to its employee within: give briefing or training of how to behave to customers of company. Textile distributor, Selendang Fajar Store in Ciawi Tasikmalaya has been able to handle its Jay Customer to become profitable customer to its company. On islamic perception, behavior of Jay Customer in Textile distributor, Selendang Fajar Store in Ciawi Tasikmalaya is not in accordance with islamic values. While their effort on facing Jay Customer is suitable with adabiyah islamic value.